Visual humanization of refugees: A visual rhetorical analysis of media discourse on the war in Ukraine - Martikainen, Jari; Sakki, Inari (British journal of social psychology, 2024)
This study examines how news images of refugees in the context of the war in Ukraine mobilize intergroup relations. A visual rhetorical analysis is used to examine the rhetorical strategies employed in news images of Ukrainian refugees in a mainstream Finnish national newspaper from February 25 to May 31, 2022. The data consisted of 465 images. The study constructed four humanizing visual rhetorical strategies based on the visual expression in news images: maternalizing, fragilizing, agonizing, and activizing. The rhetorical strategies constructed four subject positions for Ukrainian refugees: vulnerable victims, innocent victims, suffering Ukrainians, and persistent/resilient Ukrainians. All rhetorical strategies implicitly communicated the subject position of evil to Russia. The paper contributes to the current knowledge of the humanization of refugees in media discourse and the potential of media images to mobilize intergroup relations. Methodologically, the paper elaborates visual rhetorical analysis as a means of social psychological study of refugee discourse in the context of war.